The axonal endolysosomal and autophagic systems. Issue 3 (15th January 2021) - Kuijpers, Marijn; Azarnia Tehran, Domenico; Haucke, Volker; Soykan, Tolga
Abstract: Neurons, because of their elaborate morphology and the long distances between distal axons and the soma as well as their longevity, pose special challenges to autophagy and to the endolysosomal system, two of the main degradative routes for turnover of defective proteins and organelles. Autophagosomes sequester cytoplasmic or organellar cargos by engulfing them into their lumen before fusion with degradative lysosomes enriched in neuronal somata and participate in retrograde signaling to the soma. Endosomes are mainly involved in the sorting, recycling, or lysosomal turnover of internalized or membrane‐bound macromolecules to maintain axonal membrane homeostasis. Lysosomes and the multiple shades of lysosome‐related organelles also serve non‐degradative roles, for example, in nutrient signaling and in synapse formation. Recent years have begun to shed light on the distinctive organization of the autophagy and endolysosomal systems in neurons, in particular their roles in axons. We review here our current understanding of the localization, distribution, and growing list of functions of these organelles in the axon in health and disease and outline perspectives for future research. Abstract : The elaborate morphology and size of neurons, as well as their longevity, pose special challenges to autophagy and to the endolysosomal system, two of the main degradative routes for turnover of defective proteins and organelles. In this review, we discuss how axonal endosomes and autophagosomes form and select their cargo, how they are transported and mature along the axon and how they converge and join forces to mediate axonal signaling and recycling.